2020
DOI: 10.1155/2020/8883636
|View full text |Cite
|
Sign up to set email alerts
|

IL-37 Gene Modification Enhances the Protective Effects of Mesenchymal Stromal Cells on Intestinal Ischemia Reperfusion Injury

Abstract: Background. Ischemia reperfusion injury (IRI) is the major cause of intestinal damage in clinic. Although either mesenchymal stromal cells (MSCs) or interleukin 37 (IL-37) shows some beneficial roles to ameliorate IRI, their effects are limited. In this study, the preventative effects of IL-37 gene-modified MSCs (IL-37-MSCs) on intestinal IRI are investigated. Methods. Intestinal IRI model was established by occluding the superior mesenteric artery for 30 minutes and then reperfused for 72 hours in rats. Forty… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…There were also studies on MSC-derived miRNAs or circular RNAs (circRNAs) downregulating pyroptotic components in hypoxia/reoxygenation renal epithelial cells or ischemic muscle (Yuan et al, 2017;Yan et al, 2020). Besides, Kong and his group transplanted IL-37 gene-modified MSCs into rats model of intestinal ischemia-reperfusion injury and found that the expression of NLRP3 and downstream targets (cleaved caspase-1, IL-1β, and IL-18) were observably lessened (Kong et al, 2020). Overall, the underlying mechanism regarding multiple molecular pathways involved in the role of MSCs and secretome in other diseases are expected to further elucidate in ischemic stroke.…”
Section: Mscs and Pyroptosis In Ischemic Strokementioning
confidence: 99%
“…There were also studies on MSC-derived miRNAs or circular RNAs (circRNAs) downregulating pyroptotic components in hypoxia/reoxygenation renal epithelial cells or ischemic muscle (Yuan et al, 2017;Yan et al, 2020). Besides, Kong and his group transplanted IL-37 gene-modified MSCs into rats model of intestinal ischemia-reperfusion injury and found that the expression of NLRP3 and downstream targets (cleaved caspase-1, IL-1β, and IL-18) were observably lessened (Kong et al, 2020). Overall, the underlying mechanism regarding multiple molecular pathways involved in the role of MSCs and secretome in other diseases are expected to further elucidate in ischemic stroke.…”
Section: Mscs and Pyroptosis In Ischemic Strokementioning
confidence: 99%
“…In the event of I/R, intestinal immune barrier dysfunction will lead to cytokine release, intestinal inflammatory injury and bacterial invasion and migration [ 6 ], resulting in serious body damage. Many studies have demonstrated successful application of BMSCs in reducing intestinal mucosal I/R damage in animal models [ 7 , 8 ], which proposing a new strategy for the management of intestinal I/R impairments. Therefore, the application of BMSCs in IR may be fruitful and have great clinical significance.…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) possess the characteristics of immunoregulation, multidirectional differentiation potential, easy access, rapid proliferation in vitro, low activity loss after cryopreservation, low immunogenicity, and nontoxic side effects [ 5 ]. Several previous studies have demonstrated tremendous potential of MSCs in treating CIRI [ 6 ], myocardial ischemia-reperfusion injury (IRI) [ 7 ], hepatic IRI [ 8 ], intestinal IRI [ 9 ], renal IRI [ 10 ], lung IRI [ 11 ], retinal IRI [ 12 ], and spinal cord IRI [ 13 ] exhibiting specific mechanisms of action, such as angiogenesis, antiapoptosis, anti-inflammation, and tissue regeneration. In recent years, the literature supports that the paracrine mechanism of MSCs is mediated at least in part by extracellular vesicles (EVs) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%